PENGARUH AKSES DAN MOTIVASI TERHADAP PERILAKU IBU HAMIL DALAM MELAKUKAN KUNJUNGAN ANTENATAL DI WILAYAH KERJA PUSKESMAS PANCUR BATU TAHUN 2015 - Oktafiana Manurung; Ermawaty Arisandi Siallagan (STIKes Santa Elisabeth Medan, 2016)
According to the World Health Organization (WHO) Indonesian women have According to the World Health Organization (WHO) Indonesian women have very bad criteria in terms of health, marriage, employment, education, equality with men. This condition is thought to lead to low maternal access to antenatal care. Goals : Antenatal care in accordance with antenatal care standards may decrease Maternal and Infant Mortality due to regular antenatal care can detect early problems that occur in the mother during pregnancy.Methods : The type of this research is analytical descriptive with cross sectional design which aims to analyze the influence of access and motivation of pregnant mother to mother behavior in doing antenatal visit. The research was conducted in Pancur Batu Puskesmas Working Area. The population is 181 people and the sample size is 61 people. Data analysis was performed using univariate analysis, bivariate analysis with Chi-Square test, and multivariate analysis with multiple logistic regression test.Result : The result of this research indicate that physical accessibility variable is the availability of unrelated officer (p = 0,461) to mother behavior in antenatal visit, social accessibility variable (p = 0,005) and attitude (p = 0,023), and for motivation variable is motive P = 0.005) and expectations (p = 0.019) had a significant effect on maternal behavior in antenatal visits.Conclution : Based on the results of research suggested Head of Pancur Batu Puskesmas to conduct training to officers especially midwives who provide services mainly about hospitality in providing services and to officers implementing services further improve the communication of information and education so that every pregnant women have a good understanding that can eventually cause attitude Positive, high motivation and expectation that can affect the mother in conducting standardized antenatal visits.